Flash visual evoked potentials in diurnal birds of prey - Maurizio Dondi; Fabio Biaggi; Francesco Di Ianni; Pier Luigi Dodi; Fausto Quintavalla (PeerJ, 2016)
The objective of this pilot study was to evaluate the feasibility of Flash Visual Evoked Potentials (FVEPs) testing in birds of prey in a clinical setting and to describe the protocol and the baseline data for normal vision in this species. FVEP recordings were obtained from 6 normal adult birds of prey: n. 2 Harris’s Hawks (Parabuteo unicinctus), n. 1 Lanner Falcon (Falco biarmicus), n. 2 Gyrfalcons (Falco rusticolus) and n. 1 Saker Falcon (Falco cherrug). Before carrying out VEP tests, all animals underwent neurologic and ophthalmic routine examination. Waveforms were analysed to identify reproducible peaks from random variation of baseline. At least three positive and negative peaks were highlighted in all tracks with elevated repeatability. Measurements consisted of the absolute and relative latencies of these peaks (P1, N1, P2, N2, P3, and N3) and their peak-to-peak amplitudes. Both the peak latency and wave morphology achieved from normal animals were similar to those obtained previously in other animal species. This test can be easily and safely performed in a clinical setting in birds of prey and could be useful for an objective assessment of visual function.